2016
DOI: 10.1088/0957-0233/27/7/075002
|View full text |Cite
|
Sign up to set email alerts
|

Compound fault diagnosis of rotating machinery based on OVMD and a 1.5-dimension envelope spectrum

Abstract: Owing to the character of diversity and complexity, the compound fault diagnosis of rotating machinery under non-stationary operation has turned into a challenging task. In this paper, a novel method based on the optimal variational mode decomposition (OVMD) and 1.5-dimension envelope spectrum is proposed for detecting the compound faults of rotating machinery. In this method, compound fault signals are first decomposed by using OVMD containing optimal decomposition parameters, and several intrinsic mode compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
109
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 25 publications
0
109
0
Order By: Relevance
“…Hidden Markov model is extended from Markov chains to yield inferential statistical information on a state sequence [26,27]. It comprises a finite hidden state number, and each state relates to an observation at a time point.…”
Section: Hidden Markov Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Hidden Markov model is extended from Markov chains to yield inferential statistical information on a state sequence [26,27]. It comprises a finite hidden state number, and each state relates to an observation at a time point.…”
Section: Hidden Markov Modelmentioning
confidence: 99%
“…The log-likelihood probability (LL) is a fault index defined by the logarithm calculation to ( *| ) P X λ in Equation (27). The larger LL indicates the greater consistency of observation sequence to the HMM.…”
Section: Irkpca-hmm Algorithmmentioning
confidence: 99%
“…A hybrid model for denoising and bearing feature extraction using VMD was proposed recently by Zhang et al [22]. Further study on compound fault diagnosis and characteristic separation of bearings and gearbox signals were carried out by optimizing the VMD algorithm [23]. In the present work, an attempt has been made to study the influence of initialization and input parameters (bandwidth selection parameter, ) for the application pertaining to mechanical vibration signal processing.…”
Section: Introductionmentioning
confidence: 97%
“…It was also shown that statistical feature vectors from VMD are better than those obtained using EWT in SVM classification [20]. VMD was used in bearing fault analysis in [21][22][23] and the spreading in the frequency of the signal and intensity of vibration was demonstrated as a clear indication of a fault in bearings. VMD was also used in real-time power signal decomposition [24], brain magnetic resonance [25], ECG feature extraction and classification [26] and more recently in crude oil price analysis and forecasting [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation